Murine Retrovirally-transduced Bone Marrow Engraftment Models of MLL-fusion-driven Acute Myelogenous Leukemias (AML) - Stubbs, Matthew C. (Curr Protoc Pharmacol, 2017)
MLL-rearranged leukemia represents approximately 5-10% of adult AML cases and nearly half of all infant/pediatric acute leukemia cases. These leukemias have a poor prognosis, and as of yet there are no approved targeted therapeutic options. The rearrangement in the MLL gene leads to aberrant expression of MLL-fusion proteins, which are transforming in murine bone marrow, and in particular on stem cells and myeloid progenitors derived from bone marrow or fetal liver. The commonality of the MLL-fusions is the in-frame fusion of 8-11 N-terminal exons of MLL1 (KMT2a) with C-terminus of a partner fusion gene. Currently over 80 different fusion partners have been described. This protocol will focus on bone marrow-derived models only, using one particular MLL fusion, MLL-AF9, which we have used in our studies previously. These models have proven effective for drug screening, as well as for predicting clinical response.